MANAJEMEN SARANA PRASARANA PENDIDIKAN SDN 1 PENDOWO ASRI DENTE TELADAS TULANG BAWANG - Siti Khoiriyah; Sudjarwo Sudjarwo; Riswanti Rini (9 772338317006)
This research was aimed to analyze and describe the planning, purchasing, utilization, data collection, usage, maintaining and removing of facilities and infrastructure in SDN 1 Pendowo Asriand also the problems in facilities management facing by the school. This research was a case study qualitative research. The data was gained from the principal of the school, teachers, goods treasurer and committee. The result of the research showed that (1) the committee did the planning at the beginning of every academic year, (2) The purchasing was done by buying, getting donation or self-producing,(3) The data collection was done in order to enhance the process of administration and supervision, (4) The usage and maintaining was done based on the need and the rules, (5) The removing was done toward the broken or missing things, (6) The problems faced by the school dealing with the facilities and infrastructures management was the limitation of the fund and the officer did not have a good ability in handling the facilities and the infrastructures.Penelitian ini bertujuan menganalisis dan mendeskripsikan perencanaan, pengadaan, inventarisasi, penggunaan, pemeliharaan, dan penghapusan sarana prasarana di SDN 1 Pendowo Asri serta kendala yang dihadapi sekolah dalam manajemen sarana prasarana. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Sumber data diperoleh dari kepala sekolah, guru, bendahara barang, dan komite. Hasil penelitian menunjukkan bahwa (1) perencanaan dilakukan oleh panitia tiap awal tahun pelajaran, (2) pengadaan dilakukan dengan cara membeli, bantuan, dan membuat sendiri, (3) inventarisasi dilakukan dalam rangka penyempurnaan pengurusan dan pengawasan, (4) penggunaan dan pemeliharaan disesuaikan dengan kebutuhan serta mengikuti tata tertib, (7) penghapusan dilakukan terhadap sarana prasarana yang rusak atau hilang, (8) kendala yang dihadapi sekolah dalam manajemen sarana prasarana adalah keterbatasan dana, sertakompetensi petugas yang belum memadai.Kata kunci : manajemen, sarana, prasarana